KEPEMIMPINAN TRANSFORMASIONAL: STRATEGI MEMBANGUN BUDAYA INOVATIF PENDIDIKAN - Siswadi; M. Slamet Yahya; Sigit Candra Nuraziz; Alifa Muzayyana Putri (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
Leadership plays a crucial role in efforts to improve the quality of education. Transformational leadership is the ability of a leader who is charismatic, willing to take risks, inspires, motivates, and encourages members of the organization to achieve extraordinary results. This research examines how transformational leadership creates innovative, inspiring, and high-quality education to enhance educational quality. The research method used is a Systematic Literature Review (SLR), which systematically reviews the literature by identifying, analyzing, and evaluating relevant studies. The review results indicate that transformational leadership is a highly important approach for schools in their efforts to improve educational quality, as this leadership style can drive positive changes in various aspects of education. For optimal results, ongoing efforts are needed to develop transformational leadership competencies among school leaders and to create an environment that supports the implementation of this leadership style.